¿Qué hacer cuando estoy enferma? La búsqueda de alternativas para el bienestar en mujeres desplazadas, Medellín 2013-2014 (2016)
ABSTRACT: To recognize the experiences derived from the search for healthcare alternatives performed by women who have been displaced by violence and currently live in three settlements in Medellin, Colombia, during 2013-2014. Methodology: a qualitative research was conducted using grounded theory. Two types of sources were taken into account: primary sources were the discourses collected via interviews with women who have been displaced by violence and who lived in one of three settlements in Medellin at the time of this study. These interviews were applied personally and the women were culturally, ethnically and idiosyncratically diverse. The secondary sources were obtained by reviewing official documents, literature, other studies and additional material on this issue. Data were collected through semistructured interviews, focus groups and in-depth interviews. Results and Discussion: when feeling ill, women displaced by violence use traditional medicine as the first alternative to satisfy their health needs. If this is not successful, other important alternatives such as healthcare services are then used to regain well-being. When feeling healthy, these women try to keep interacting with these alternatives in order to ensure that their current health status does not change. Conclusions: women displaced by violence perceive health and illness in a way that allows them to interact with different alternatives for the preservation or recovery of their health status.